Recurrent Venous Thromboembolism in Patients on Anticoagulation: An Update Based on the Revised AWMF S2k Guideline - Klamroth, Robert; Riess, Hanno; Beyer-Westendorf, Jan; Linnemann, Birgit (Hämostaseologie, 2024)
In the recently updated German S2k Guideline “Diagnostics and Therapy of Venous Thrombosis and Pulmonary Embolism,” a new chapter was incorporated about recurrent venous thromboembolism (VTE) in patients on anticoagulation treatment. Despite the high efficacy of anticoagulation in most patients, approximately 2% experience a recurrent VTE event while receiving anticoagulant drugs. The proper diagnosis of the recurrent VTE is important and possible only with the knowledge of localization and thrombus burden of the primary VTE event. Possible reasons for recurrent VTE events in patients on anticoagulation are non-adherence to medication, sub-therapeutic drug levels due to resorption disorders or drug interactions, or concomitant disease with high thrombogenicity. Cancer is the most common underlying disease, but it is important to investigate and understand possible other causes whenever a breakthrough VTE event occurs. This results in the recommendation that in patients with VTE recurrence on therapeutic anticoagulation, in particular, the presence of malignant disease, antiphospholipid syndrome, and rare diseases like paroxysmal nocturnal hemoglobinuria or Behçet's disease should be considered. For VTE recurrence during heparin therapy, heparin-induced thrombocytopenia type II needs to be ruled out, even if platelet counts are within the normal range. Although the mechanisms of recurrence on anticoagulation can be evaluated in a certain degree, clinical evidence for the management of recurrent VTE in anticoagulated patients is minimal and mainly based on expert opinion. Switching anticoagulant medication and intensifying anticoagulant treatment are possible options.
Keywords: venous thromboembolism; recurrent thrombosis; anticoagulation